One public health strategy fits all needs? Regional Diversity in Health Policy - Więckowska, Barbara; Raulinajtys-Grzybek, Monika; Korporowicz-Żmichowska, Violetta; Raczek-Żeromska, Melanie (Studia z Polityki Publicznej, 2024)
In Poland, there are numerous diversity in the field of population health. They are often linked not only to socio-economic status but also to location. The disparities occur between regions as well as within regions. The disparities occur between regions as well as within regions. Eliminating these disproportions is also the responsibility of public authorities in the field of, for example, spatial policy in order to improve the living conditions of the community, including improving the health of the population. The aim of this study is to attempt to determine whether there are differences in health in spatial terms, especially differences between cities with county rights, in connection with health programs implemented by these cities. For the purposes of this study, was analyzed health policy programs that received a positive or conditionally positive opinion from the President of the Agency for Health Technology Assessment and Tariffication and were implemented in the year 2020.The findings have demonstrated significant variations in the number of health programs both between regions and within individual regions, underscoring the need for a nuanced and tailored approach to public health strategies.